Learning motivation: its impact on learning management and lecturer performance - Aprizal, Yobi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to measure the significant effect of learning management on student learning motivation at the College of Tarbiyah Pringsewu, Lampung, Indonesia, measure the significant effect of lecturer performance on student learning motivation at STIT Pringsewu and measure the significant effect of learning management and lecturer performance together on student learning motivation at STIT Pringsewu. This type of research is quantitative with a population of 134 students and a research sample of 100 students. The sample in this study used probability sampling technique, and data collection using a questionnaire. The results showed that the p-value (Sig.) of the learning management variable X1 of 0.000 was smaller than 0.05. The t-count value is greater than the t-test. The tcount value is greater than the ttable, which is 5.162 greater than 1.985. The p-value (Sig.) of the lecturer performance variable X2 of 0.00 is smaller than 0.05. The tcount result is greater than the ttable, namely 4.317 greater than 1.985. The p-value (Sig.) of variable X1 learning management of 0.000 and X2 lecturer performance of 0.000 is smaller than 0.05. It is concluded that there is a significant effect of learning management on student learning motivation at STIT Pringsewu, there is a significant effect of lecturer performance on student learning motivation at STIT Pringsewu, and there is a significant effect of learning management and lecturer performance on student learning motivation at STIT Pringsewu.